The Mica Philly Principle and Political Corruption in Society (Sebha University Conference Proceedings, 2022)
This research dealt with one of the major issues that most societies suffer from. It is the issue of corruption in general and political corruption in particular. It is one of the issues of importance, specifically at the local level, where it has pervaded the structures of the state administrative, political, economic and even social. It forced us to look for its causes and mechanisms to combat it. Some rulers and politicians have taken principles that may have been useful in the  time and their owners, but they are far from our current time, and completely contrary to our morals and principles, and go beyond it. For our true religion, it is not constrained by custom or conscience, including the principle of the end justifying the means to Mika Philly. They found their way, justifying their abhorrent actions and maintaining their authority to show the extent to which our rulers are influenced by this principle. They are accused of managing the affairs of the state that led to political corruption, and asked to Indicate ways to combat this corruption.